2011
DOI: 10.1182/blood-2010-08-300160
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage–induced transcriptional program in CLL: biological and diagnostic implications for functional p53 testing

Abstract: The DNA damage pathway plays a central role in chemoresistance in chronic lymphocytic leukemia (CLL), as indicated by the prognostic impact of TP53 and ATM loss/ mutations. We investigated the function of the p53 axis in primary CLL samples by studying p53 and p21 responses to irradiation by FACS and RT-PCR. We observed a distinct response pattern for most cases with a 17p deletion (n ‫؍‬ 16) or a sole TP53 mutation (n ‫؍‬ 8), but not all cases with a p53 aberration were detected based on a number of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 44 publications
(60 reference statements)
2
28
0
Order By: Relevance
“…The chromosomal defects associated with aggressive CLL include deletion of 17p13 (17p137) and 11q22 (11q227), which result in loss of one allele of TP53 or ATM, respectively. This suggests that defective DNA damage responses in CLL cells could result in a poorer outcome, an association that is further supported by the findings that almost all patients with 17p137 with progressive CLL have a dysfunctional mutation in the remaining TP53, and that patients with bi-allelic loss of function of TP53 in the absence of 17p137 also have a very poor prognosis [5]. In addition, patients with CLL with 11q227 and loss of function of the remaining ATM allele have a very poor prognosis [6].…”
supporting
confidence: 58%
“…The chromosomal defects associated with aggressive CLL include deletion of 17p13 (17p137) and 11q22 (11q227), which result in loss of one allele of TP53 or ATM, respectively. This suggests that defective DNA damage responses in CLL cells could result in a poorer outcome, an association that is further supported by the findings that almost all patients with 17p137 with progressive CLL have a dysfunctional mutation in the remaining TP53, and that patients with bi-allelic loss of function of TP53 in the absence of 17p137 also have a very poor prognosis [5]. In addition, patients with CLL with 11q227 and loss of function of the remaining ATM allele have a very poor prognosis [6].…”
supporting
confidence: 58%
“…However, there are at least 3 possible explanations for this observation. First, different TP53 mutations result in varying degrees of baseline p53 protein overexpression (32,33). In keeping with this idea, all 3 samples in this study with frameshift or truncation mutations were classified as type B in the functional assay, likely reflecting the lack of expression of full-length p53 protein from the mutated allele in these cases (Supplementary Table S3).…”
Section: Discussionmentioning
confidence: 83%
“…However, previous studies from this and other groups have shown that p53 pathway defects can be caused by other mechanisms (25,26,32). This study therefore sought to establish whether functional analysis of the ATM-p53-p21 pathway has prognostic value in CLL and, if so, whether it adds to the information provided by currently available prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…12 Our analysis recorded almost identically reduced TTFT in groups with sole 11q-and ATM mutation in comparison with wt patients. A potential explanation for the observed clinical impact of sole 11q-may possibly result from a gene dosage effect of ATM 12,45,46 or other genes located in deleted region at 11q, 13 or from mutations affecting genes like BIRC3 located at 11q. This gene could be an interesting candidate because its mutations are recurrent in CLL and have been recognized as mutually exclusive with TP53 defects, 47 similarly to ATM mutations.…”
Section: Discussionmentioning
confidence: 99%